TLR 2, TLR 4, ROS, óxido nítrico, P38 e IKK em células mononucleares de cães com leishmaniose Visceral tratadas com o imunomodulador P-MAPA: Larissa Martins Melo. - - Melo, Larissa Martins [UNESP] (2014)
Visceral leishmaniasis (VL) in Brazil represents a serious public health problem; therefore, it is important to study new alternatives to treat infected dogs. The immunomodulator protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride (P-MAPA) improves immunocompetence when the immune system is impaired, but its dependence on Toll-like receptors (TLRs) and the mechanisms involved in the immune response remain unclear. The in vitro action of P-MAPA on the expression of TLR2 and TLR4, reactive oxygen species (ROS), nitric oxide (NO) and p38 mitogen-activated protein kinase (p38MAPK) and IKK phosphorylation were studied in mononuclear cells from peripheral blood and macrophages from healthy and Leishmania-infected dogs. The PBMC or macrophages were isolated and cultured with different concentrations of P-MAPA (20,100 and 200 μg/mL) in a humid environment at 37°C with 5% CO2. Observation revealed that Leishmania-infected dogs showed a decrease in TLR2 in macrophages compared with healthy dogs and in induction with P-MAPA. ROS were increased in PBMCs from Leishmania sp.-infected dogs compared with healthy dogs and P-MAPA improved ROS production. NO production was increased in culture supernatant from macrophages stimulated by P-MAPA in both healthy and Leishmania-infected dogs. Treatment of macrophages from healthy dogs with immunomodulatory P-MAPA induced p38 MAPK and IKK phosphorylation, suggesting signal transduction by this pathway. These findings suggest that P-MAPA has potential as a therapeutic drug in the treatment of canine visceral leishmaniasis